Lightweight automobile trunk carpet and preparation method thereof

By preparing modified polyester fibers and combining them with polypropylene foaming materials, the existing automobile suitcase carpets have solved the problems of large weight and poor wear resistance, and high-strength, wear-resistant and lightweight carpet preparation is achieved, meeting the lightweight needs of the automobile industry.

CN116100897BActive Publication Date: 2025-03-11CHANGSHU XINCHANGTI AUTOMOBILE INTERIOR TRIM TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211068871.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-02
Publication Date
2025-03-11
Estimated Expiration
2042-09-02

AI Technical Summary

Technical Problem

Due to the large weight of materials, shrinkage volume, poor wear resistance, poor wear resistance, it is difficult to meet the needs of lightweight, energy-saving and environmentally friendly due to the large material weight, shrinkage volume, and poor fabric layer strength.

Method used

By preparing hydroxyl-containing unsaturated polyester and reacting with ABS, allyl glycidyl ether, and thiol polysiloxane, we form modified polyester fibers and combine with polypropylene foaming material to prepare a high-strength, wear-resistant and lightweight suitcase carpet.

Benefits of technology

It has achieved the lightweight, wear resistance and toughness of car suitcase carpets, and met the goals of lightweight, energy-saving and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003828808370000151
    Figure BDA0003828808370000151
  • Figure BDA0003828808370000161
    Figure BDA0003828808370000161
Patent Text Reader

Abstract

The present invention discloses a lightweight car trunk carpet and a preparation method thereof, comprising the following processes: (1) preparation of a surface non-woven fabric: reacting an unsaturated polyester with a mercapto polysiloxane to obtain a modified polyester; spinning the modified polyester to obtain a modified polyester fiber; mixing the modified polyester fiber, spunlacing, and obtaining a non-woven fabric; slurrying the non-woven fabric, and drying to obtain a surface non-woven fabric; (2) preparation of a car trunk carpet: placing two layers of surface non-woven fabric on the upper and lower surfaces of a mold cavity, respectively, and injecting a polypropylene foam material into the mold cavity to obtain a trunk carpet. The present invention prepares a hydroxyl-containing unsaturated polyester by using a dibasic acid and an unsaturated diol, reacting the hydroxyl-containing unsaturated polyester with ABS, allyl glycidyl ether, and mercapto polysiloxane in sequence to prepare a modified polyester, spinning, spunlacing, slurrying, obtaining a surface non-woven fabric, and compounding with a polypropylene foam material to obtain a high-strength, wear-resistant, and lightweight trunk carpet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of automobile interior decoration parts, in particular to a lightweight automobile luggage compartment carpet and a preparation method thereof. Background Art

[0002] Lightweight, energy-saving, environmentally friendly, efficient and low-cost production have always been the goals that the automotive industry continues to pursue. As a utility room and storage room of a car, the trunk of a car is also an object of lightweight processing, and the trunk carpet is even more so as an interior decoration part of the trunk of a car. However, some existing trunk carpets are made of a composite of wood and fabric layers, which have the problems of heavy weight and volume shrinkage. The fabric layer is mostly non-woven fabric, and the strength and wear resistance are not optimistic. Therefore, we propose a lightweight trunk carpet for cars and a preparation method thereof. Summary of the invention

[0003] The object of the present invention is to provide a lightweight automobile trunk carpet and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a lightweight automobile trunk carpet, comprising the following processes:

[0005] (1) Preparation of surface nonwoven fabric:

[0006] Taking dibasic acid, unsaturated diol and saturated diol to prepare hydroxyl-containing unsaturated polyester; reacting and grafting the hydroxyl-containing unsaturated polyester with ABS to obtain hydroxyl-containing polyester;

[0007] The hydroxyl-containing polyester is reacted with allyl glycidyl ether to obtain an unsaturated polyester; the unsaturated polyester is reacted with mercapto polysiloxane to obtain a modified polyester;

[0008] Spinning the modified polyester to obtain modified polyester fibers; mixing the modified polyester fibers, spunlacing, and obtaining non-woven fabrics; impregnating the non-woven fabrics with slurry, and drying, to obtain surface non-woven fabrics;

[0009] (2) Preparation of car trunk carpet:

[0010] Two layers of surface non-woven fabrics are placed on the upper surface and the lower surface of the inner cavity of the mold respectively, and polypropylene foam material is injected into the inner cavity of the mold to obtain a luggage compartment carpet.

[0011] Furthermore, the (1) comprises the following process:

[0012] 1.1. Preparation of modified polyester:

[0013] The dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and polymerization inhibitor are mixed, heated to 130-220°C at a heating rate of 2-3°C / min, reacted until esterification water appears, heated to 230-250°C at a heating rate of 10-16°C / h, reacted at a constant temperature until the acid value reaches 0-2.0 mgKOH / g, and a hydroxyl-containing unsaturated polyester is obtained;

[0014] The hydroxyl-containing unsaturated polyester, ABS and AIBN are mixed, and kneaded at a temperature of 180 to 200° C. and a rotation speed of 80 to 120 rpm for 8 to 10 minutes to obtain the hydroxyl-containing polyester;

[0015] Take the hydroxyl-containing polyester, add tetrahydrofuran, allyl glycidyl ether, toluene, and phosphazene base under the protection of argon atmosphere, and react at a constant temperature of 50-60°C for 48 hours to obtain an unsaturated polyester;

[0016] In a nitrogen atmosphere, mercaptopropylmethyldimethoxysilane, anhydrous ethanol and deionized water were mixed, the pH was adjusted to 5-6 with hydrochloric acid, the temperature was raised to 58-64° C., the reaction was carried out for 3.5-4.5 hours, and the mixture was dried in vacuum to obtain mercaptopolysiloxane;

[0017] Take mercaptopolysiloxane, unsaturated polyester and azobisisobutyronitrile, and knead them at a speed of 80 to 120 rpm for 8 to 10 minutes in a nitrogen atmosphere at a kneading temperature of 180 to 200° C. to obtain a modified polyester;

[0018] 1.2. Preparation of surface non-woven fabric:

[0019] The modified polyester and polyethylene oxide are mixed, N,N-dimethylformamide and water are added, and the mixture is stirred at 50-60°C for 12-24 hours to obtain a spinning solution; the electrospinning process is as follows: the voltage is 9-15 kV, the receiving distance is 10-20 cm, and the propulsion speed of the micro-flow injection pump is 1.0-2.0 mL / h; the water washing process is as follows: ultrasonic water washing at 55-65°C for 30-60 minutes, and vacuum drying at 70-75°C for 30-60 minutes to obtain the modified polyester fiber;

[0020] The modified polyester fibers are mixed, carded, laid, and spunlace to obtain a non-woven fabric; the non-woven fabric is impregnated with slurry and dried to obtain a surface non-woven fabric.

[0021] In the above technical scheme, the dibasic acid terephthalic acid, unsaturated diols, and saturated diols react and polymerize in the presence of a catalyst and an inhibitor to obtain an unsaturated polyester with hydroxyl groups, namely, a hydroxyl-containing unsaturated polyester. Under the action of an initiator, the hydroxyl-containing unsaturated polyester undergoes an addition reaction with ABS to obtain a hydroxyl-containing polyester, which can improve the shrinkage of the prepared modified polyester; at the same time, the hydroxyl-containing unsaturated polyester is strengthened and toughened, and the mechanical properties of the hydroxyl-containing polyester are improved, and its thermal stability is improved. Introducing ABS into the polyester system can improve the mechanical properties of the product; the hydroxyl-containing polyester is mixed with allyl glycidyl ether, so that the hydroxyl groups therein react with the epoxy groups to obtain an unsaturated polyester with a double bond side chain, further increasing its molecular weight, and helping to improve its mechanical properties, high temperature resistance, and corrosion resistance. The double bonds in the unsaturated polyester undergo a click reaction with the mercapto groups in the mercapto polysiloxane, and the mercapto-containing polysiloxane is introduced into the modified polyester system, which helps to improve the mechanical properties of the modified polyester and improve its low-temperature impact resistance. Polyethylene oxide is used as a template, a modified polyester spinning solution is prepared for electrostatic spinning, and the water-soluble material polyethylene oxide is removed by washing to obtain a modified polyester fiber with a micro-nano porous structure and a certain degree of roughness. This is beneficial to improving the adhesion between the prepared non-woven fabric and the polyurethane coating produced in the subsequent process, and can coordinate the component configuration of the modified polyester fiber to effectively reduce the weight of the fiber itself.

[0022] Furthermore, the unsaturated diol in 1.1. is one or more of butene diol, 1,5-hexadiene-3,4-diol, 1,5-hexadiene-2,3-diol, 1,5-hexadiene-2,5-diol, 2-vinyl propane-1,3-diol, and 1,7-octadiene-2,6-diol;

[0023] The saturated diol is one of ethylene glycol and pentanetriol or a mixture of the two;

[0024] The polymerization inhibitor is one of hydroquinone, p-benzoquinone, methyl hydroquinone, p-hydroxyanisole, 2-tert-butylhydroquinone, 4-tert-butylcatechol, and 2,5-di-tert-butylhydroquinone;

[0025] The catalyst is one of monobutyltin oxide, dibutyltin oxide, stannous octoate, dibutyltin dilaurate, tetraisopropyl titanate and tetra-n-butyl titanate.

[0026] Furthermore, the mass ratio of the dibasic acid terephthalic acid, the unsaturated diol, the saturated diol, the catalyst and the inhibitor in 1.1. is 100:(40-100):(18-96):(0.1-0.4):(0.016-0.023).

[0027] Furthermore, the mass ratio of the hydroxyl-containing unsaturated polyester, ABS (acrylonitrile-butadiene-styrene copolymer), and AIBN (azobisisobutyronitrile) in 1.1. is 100:(12-18):(0.5-0.8).

[0028] Furthermore, the mass ratio of the hydroxyl-containing polyester, allyl glycidyl ether, and phosphazene base in 1.1. is 1:(0.9-1.0):(18.2-18.6);

[0029] The volume ratio of tetrahydrofuran to toluene is (20-25):1;

[0030] The ratio of modified polyester to tetrahydrofuran is (1.6-2.0) g / mL.

[0031] Furthermore, the mass ratio of modified polyester to polyethylene oxide is 100:(6-10); the mass ratio of N,N-dimethylformamide to water is 100:(0.95-3.92), and the solid content of the spinning solution is 20.0-26.0%.

[0032] Furthermore, the mass ratio of anhydrous ethanol to deionized water is (5.5-6.2):1.

[0033] Furthermore, the molar ratio of mercaptopropylmethyldimethoxysilane, allyl glycidyl ether, and azobisisobutyronitrile is (0.8-1.1):1:(0.03-0.05).

[0034] Furthermore, the length of the modified polyester fiber is 40 to 51 mm.

[0035] Furthermore, the slurry dipping process in 1.2 is as follows:

[0036] Take toluene diisocyanate, dibutyltin dilaurate, and ethyl acetate, heat to 50-55° C., slowly add trimethylolpropane in a nitrogen atmosphere, heat to 75-80° C., react for 2.0-2.5 hours, and obtain a polyurethane prepolymer;

[0037] In a nitrogen atmosphere, diethanolamine and N,N-dimethylacetamide were mixed, and a solution of succinic anhydride in N,N-dimethylacetamide was slowly added, and the mixture was reacted for 3.6 to 4.5 hours to obtain a monomer; the monomer and hydroxyl-containing polyester were mixed, and p-toluenesulfonic acid and toluene were added, and the mixture was heated to 140 to 145°C, and the mixture was refluxed for 7 to 8 hours to obtain a modified amide;

[0038] Take N,N-dimethylacetamide, add polyurethane prepolymer, modified amide, and benzylamine peroxide, mix, and obtain an impregnation solution;

[0039] Immerse the nonwoven fabric in the impregnation solution for 10 to 15 seconds, slowly pull it out, react at 80 to 90°C for 30 to 60 minutes, wash with water, and dry.

[0040] In the above technical scheme, toluene diisocyanate and trimethylolpropane react under the action of a catalyst to obtain a -NCO-terminated polyurethane prepolymer; diethanolamine and succinic anhydride react to obtain an amide monomer containing carboxyl and hydroxyl groups. The prepared monomer and hydroxyl-containing polyester undergo esterification reaction in the presence of a catalyst and a water-carrying agent to generate an unsaturated polyamide ester with a hyperbranched, three-dimensional network structure-modified amide, which contains a large number of active groups at its end. The polyurethane prepolymer is mixed with the unsaturated polyamide ester, and the subsequent -NCO reacts with the hydroxyl group to obtain a polyurethane coating with a carbamate structure and an unsaturated polyamide ester structure. Among them, the active hydrogen on the secondary amine can react with excess -NCO to generate allophanate, and the double bond in the modified amide can also undergo free radical polymerization with the active hydrogen in the urethane bond, excess -NCO and other groups to generate a spatial network molecular structure, so that the curing rate, curing degree and mechanical strength of the prepared coating are improved. As the molecular weight of the modified amide increases, the bending strength of the prepared polyurethane coating increases; the increase in the number of double bonds increases the number of crosslinking points between the modified amide and the polyurethane prepolymer, the rigidity of the polyurethane coating is improved, and the wear resistance is enhanced. The increase in the mass ratio (NCO / OH ratio) between the polyurethane prepolymer and the modified amide increases the number of hydrogen bonds in the molecule, the hardness and tensile strength of the prepared polyurethane coating are improved, the NH specific gravity increases, and the overall polarity of the molecule is high, which improves the adhesion of the coating on the non-woven fabric. If the mass ratio between the polyurethane prepolymer and the modified amide is too high, -NCO will react with moisture in the air to produce carbon dioxide, causing bubbles in the coating, which will affect the appearance and adhesion of the prepared polyurethane coating; if the mass ratio between the polyurethane prepolymer and the modified amide is too low, urea groups, polyisocyanate groups, etc. cannot be generated during the curing of the coating, which will lead to a decrease in the adhesion of the prepared polyurethane coating; the appropriate NCO / OH ratio can make the polyurethane coating have both high strength and high toughness. The presence of a large number of cavities in the modified amide can stabilize and encapsulate the free radicals in the polyurethane coating, inhibiting the aging of the coating; the surface non-woven fabric has water resistance, wear resistance, chemical resistance and good toughness, and its bursting strength is improved.

[0041] Furthermore, the mass ratio of toluene diisocyanate, trimethylolpropane and dibutyltin dilaurate is 100:(24-27):(0.8-1.0);

[0042] The ratio of toluene diisocyanate to ethyl acetate is (0.25 to 0.30) g / mL.

[0043] Furthermore, the molar ratio of diethanolamine to succinic anhydride is 1:1.

[0044] The ratio of diethanolamine to N,N-dimethylacetamide is (0.60 to 0.90) g / mL.

[0045] The ratio of succinic anhydride to N,N-dimethylacetamide in the N,N-dimethylacetamide solution of succinic anhydride is (0.20 to 0.25) g / mL.

[0046] Furthermore, the molar ratio of the monomer, the hydroxyl-containing polyester, p-toluenesulfonic acid and toluene is 100:(200-600):(4.5-5.3):(1.7-2.0).

[0047] Furthermore, the mass ratio of the polyurethane prepolymer, the modified amide and the benzylamine peroxide is 100:(10-20):(0.7-1.0).

[0048] Furthermore, the polypropylene foam material includes the following components by weight: 66 parts of polypropylene, 5.0 parts of POE, 25 parts of filler, 1.0 part of nucleating agent, 2 parts of odor remover, 1.0 part of anti-aging agent, and 1.5 parts of foaming agent.

[0049] Furthermore, the preparation process of the polypropylene foam material is: polypropylene, POE, filler, nucleating agent, odor remover, and anti-aging agent are mixed evenly, twin-screw extrusion granulation is performed to form masterbatch, and then mixed with the foaming agent.

[0050] Furthermore, the filler is zinc oxide, the nucleating agent is 500 mesh talc, the odor remover is aluminosilicate, the antioxidant is a mixture of antioxidant 168 and antioxidant 1010, and the mass ratio of antioxidant 168 to antioxidant 1010 is 1:1.

[0051] Furthermore, the foaming agent includes the following weight components: 2.0 parts of azodicarbonamide, 0.08 parts of zinc oxide, 1.0 parts of sodium bicarbonate, and 0.2 parts of citric acid; the preparation process is: mix azodicarbonamide, zinc oxide, sodium bicarbonate, and citric acid, and pass through a 100-mesh sieve.

[0052] Furthermore, the injection molding process is as follows: the extrusion temperature of the polypropylene foam material is 210° C., the injection molding speed is 100 mm / s, and the cooling time is 20 s.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] The lightweight automobile trunk carpet and preparation method thereof of the present invention comprises the following steps: preparing a hydroxyl-containing unsaturated polyester by using a dibasic acid and an unsaturated diol, reacting the hydroxyl-containing unsaturated polyester with ABS, allyl glycidyl ether and mercaptopolysiloxane in sequence to prepare a modified polyester, spinning, hydroentangling and slurry impregnation to obtain a surface non-woven fabric, and compounding the non-woven fabric with a polypropylene foam material to obtain a highly tough, wear-resistant and lightweight trunk carpet. DETAILED DESCRIPTION

[0055] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] Example 1

[0057] (1) Preparation of surface nonwoven fabric:

[0058] 1.1. Preparation of modified polyester:

[0059] Take dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and polymerization inhibitor, mix them, heat them to 130°C at a heating rate of 2°C / min, react until esterification water appears, heat them to 230°C at a heating rate of 10°C / h, and react at a constant temperature until the acid value reaches 2.0 mgKOH / g to obtain hydroxyl-containing unsaturated polyester; the unsaturated diol is an equal-mass mixture of 1,5-hexadiene-2,5-diol, 2-vinylpropane-1,3-diol and 1,7-octadiene-2,6-diol; the saturated diol is ethylene glycol; the polymerization inhibitor is hydroquinone; the catalyst is monobutyl tin oxide; the mass ratio of dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and polymerization inhibitor is 100:40:96:0.1:0.016;

[0060] The hydroxyl-containing unsaturated polyester, ABS and AIBN were mixed, and kneaded at 180° C. and 80 rpm for 8 minutes to obtain the hydroxyl-containing polyester; the mass ratio of the hydroxyl-containing unsaturated polyester, ABS and AIBN was 100:12:0.5;

[0061] Take a hydroxyl-containing polyester, add tetrahydrofuran, allyl glycidyl ether, toluene, and phosphazene base under the protection of argon atmosphere, and react at a constant temperature of 50°C for 48 hours to obtain an unsaturated polyester; the mass ratio of hydroxyl-containing polyester, allyl glycidyl ether, and phosphazene base is 1:0.9:18.2; the volume ratio of tetrahydrofuran and toluene is 20:1; the ratio of modified polyester and tetrahydrofuran is 1.6 g / mL;

[0062] In a nitrogen atmosphere, mercaptopropyl methyl dimethoxy silane, anhydrous ethanol and deionized water were mixed, the pH was adjusted to 6 with hydrochloric acid, the temperature was raised to 58°C, the reaction was performed for 3.5 hours, and vacuum dried to obtain mercapto polysiloxane; the mass ratio of anhydrous ethanol to deionized water was 5.5:1; mercapto polysiloxane, unsaturated polyester and azobisisobutyronitrile were mixed and kneaded at a speed of 80 rpm for 8 minutes in a nitrogen atmosphere at a kneading temperature of 180°C to obtain modified polyester; the molar ratio of mercaptopropyl methyl dimethoxy silane, allyl glycidyl ether and azobisisobutyronitrile was 0.8:1:0.03;

[0063] 1.2. Preparation of surface non-woven fabric:

[0064] The modified polyester and polyethylene oxide were mixed, N,N-dimethylformamide and water were added, and the mixture was stirred at 50°C for 12 hours to obtain a spinning solution; the electrospinning process was as follows: the voltage was 9 kV, the receiving distance was 10 cm, and the propulsion speed of the micro-flow injection pump was 1.0 mL / h; the water washing process was as follows: ultrasonic water washing at 55°C for 30 minutes, and vacuum drying at 70°C for 30 minutes to obtain the modified polyester fiber;

[0065] The mass ratio of modified polyester and polyethylene oxide is 100:6; the mass ratio of N,N-dimethylformamide and water is 100:0.95, and the solid content of the spinning solution is 20.0%;

[0066] The modified polyester fibers are mixed, carded, laid, and spunlace to obtain a non-woven fabric; the length of the modified polyester fibers is 40 mm; the weight of the non-woven fabric is 80 g / m 2 ;

[0067] Take toluene diisocyanate, dibutyltin dilaurate, and ethyl acetate, heat to 50°C, slowly add trimethylolpropane in a nitrogen atmosphere, heat to 75°C, and react for 2.0 hours to obtain a polyurethane prepolymer;

[0068] The mass ratio of toluene diisocyanate, trimethylolpropane, and dibutyltin dilaurate is 100:24:0.8; the ratio of toluene diisocyanate and ethyl acetate is 0.25 g / mL;

[0069] In a nitrogen atmosphere, diethanolamine and N,N-dimethylacetamide were mixed, and a solution of succinic anhydride in N,N-dimethylacetamide was slowly added, and the mixture was reacted for 3.6 hours to obtain a monomer; the monomer and hydroxyl-containing polyester were mixed, and p-toluenesulfonic acid and toluene were added, and the mixture was heated to 140°C and refluxed for 7 hours to obtain a modified amide;

[0070] The molar ratio of diethanolamine to succinic anhydride is 1:1; the ratio of diethanolamine to N,N-dimethylacetamide is 0.60 g / mL; the ratio of succinic anhydride to N,N-dimethylacetamide in the N,N-dimethylacetamide solution of succinic anhydride is 0.20 g / mL; the molar ratio of the monomer, the hydroxyl-containing polyester, p-toluenesulfonic acid, and toluene is 100:200:4.5:1.7;

[0071] Take N,N-dimethylacetamide, add polyurethane prepolymer, modified amide, and benzylamine peroxide, mix, and obtain an impregnation solution;

[0072] The mass ratio of polyurethane prepolymer, modified amide and benzyl peroxide is 100:10:0.7; the solid content of the impregnation liquid is 10%;

[0073] The non-woven fabric was immersed in the impregnation solution for 10 seconds, slowly pulled out, reacted at 80°C for 30 minutes, washed with water, and dried to obtain a surface non-woven fabric;

[0074] (2) Preparation of car trunk carpet:

[0075] Two layers of surface non-woven fabrics are placed on the upper surface and the lower surface of the mold cavity respectively, and polypropylene foam material is injected into the mold cavity. The injection molding process is: the extrusion temperature of the polypropylene foam material is 210°C, the injection molding speed is 100mm / s, and the cooling time is 20s; molding, and obtaining a luggage compartment carpet;

[0076] The polypropylene foam material is a polypropylene foam material, and the polypropylene foam material includes the following components by weight: 66 parts of polypropylene, 5.0 parts of POE, 25 parts of filler, 1.0 part of nucleating agent, 2 parts of odor remover, 1.0 part of anti-aging agent, and 1.5 parts of foaming agent; the foaming agent includes the following components by weight: 2.0 parts of azodicarbonamide, 0.08 parts of zinc oxide, 1 part of sodium bicarbonate, and 0.2 parts of citric acid.

[0077] Example 2

[0078] (1) Preparation of surface nonwoven fabric:

[0079] 1.1. Preparation of modified polyester:

[0080] The dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and polymerization inhibitor are mixed, the temperature is raised to 175°C at a heating rate of 150°C / h, the reaction is carried out until esterification water appears, the temperature is raised to 240°C at a heating rate of 13°C / h, and the reaction is carried out at a constant temperature until the acid value reaches 1.0 mgKOH / g, thereby obtaining a hydroxyl-containing unsaturated polyester;

[0081] The unsaturated diol is a mixture of 1,5-hexadiene-3,4-diol, 1,5-hexadiene-2,3-diol and 1,5-hexadiene-2,5-diol in equal weights; the saturated diol is pentatriol; the inhibitor is p-benzoquinone; the catalyst is dibutyltin dilaurate; the mass ratio of dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and inhibitor is 100:70:58:0.2:0.02;

[0082] The hydroxyl-containing unsaturated polyester, ABS and AIBN were mixed, and kneaded at a speed of 100 rpm for 9 minutes at a kneading temperature of 190° C. to obtain a hydroxyl-containing polyester;

[0083] The mass ratio of hydroxyl-containing unsaturated polyester, ABS, and AIBN is 100:15:0.7;

[0084] Take the hydroxyl-containing polyester, add tetrahydrofuran, allyl glycidyl ether, toluene, and phosphazene base under the protection of argon atmosphere, and react at 55°C for 48 hours to obtain unsaturated polyester;

[0085] The mass ratio of hydroxyl-containing polyester, allyl glycidyl ether, and phosphazene base is 1:0.95:18.4; the volume ratio of tetrahydrofuran and toluene is 22:1; the ratio of modified polyester and tetrahydrofuran is 1.8 g / mL;

[0086] In a nitrogen atmosphere, mercaptopropylmethyldimethoxysilane, anhydrous ethanol and deionized water were mixed, the pH was adjusted to 5.5 with hydrochloric acid, the temperature was raised to 60°C, the reaction was performed for 4 hours, and the mixture was dried in vacuo to obtain mercaptopolysiloxane; the mass ratio of anhydrous ethanol to deionized water was 5.8:1;

[0087] Take mercaptopolysiloxane, unsaturated polyester and azobisisobutyronitrile, and knead them at a speed of 100 rpm for 9 minutes in a nitrogen atmosphere at a kneading temperature of 190° C. to obtain a modified polyester; the molar ratio of mercaptopropylmethyldimethoxysilane, allyl glycidyl ether and azobisisobutyronitrile is 1:1:0.04;

[0088] 1.2. Preparation of surface non-woven fabric:

[0089] The modified polyester and polyethylene oxide were mixed, N,N-dimethylformamide and water were added, and the mixture was stirred at 55°C for 18 hours to obtain a spinning solution; the electrospinning process was as follows: the voltage was 12 kV, the receiving distance was 15 cm, and the propulsion speed of the micro-flow injection pump was 1.5 mL / h; the water washing process was as follows: ultrasonic water washing at 60°C for 45 minutes, and vacuum drying at 72°C for 45 minutes to obtain the modified polyester fiber;

[0090] The mass ratio of modified polyester and polyethylene oxide is 100:8; the mass ratio of N,N-dimethylformamide and water is 100:2.55, and the solid content of the spinning solution is 23.0%;

[0091] The modified polyester fibers are mixed, carded, laid, and spunlace to obtain a non-woven fabric; the length of the modified polyester fibers is 45 mm; the weight of the non-woven fabric is 100 g / m 2 ;

[0092] Take toluene diisocyanate, dibutyltin dilaurate, and ethyl acetate, heat to 52°C, slowly add trimethylolpropane in a nitrogen atmosphere, heat to 78°C, react for 2.2 hours, and obtain a polyurethane prepolymer;

[0093] The mass ratio of toluene diisocyanate, trimethylolpropane, and dibutyltin dilaurate is 100:25:0.9;

[0094] The ratio of toluene diisocyanate to ethyl acetate is 0.27 g / mL;

[0095] In a nitrogen atmosphere, diethanolamine and N,N-dimethylacetamide were mixed, and a solution of succinic anhydride in N,N-dimethylacetamide was slowly added, and the mixture was reacted for 4 hours to obtain a monomer; the monomer and hydroxyl-containing polyester were mixed, and p-toluenesulfonic acid and toluene were added, and the mixture was heated to 142°C and refluxed for 7.5 hours to obtain a modified amide;

[0096] The molar ratio of diethanolamine to succinic anhydride is 1:1; the ratio of diethanolamine to N,N-dimethylacetamide is 0.75 g / mL; the ratio of succinic anhydride to N,N-dimethylacetamide in the N,N-dimethylacetamide solution of succinic anhydride is 0.22 g / mL; the molar ratio of the monomer, the hydroxyl-containing polyester, p-toluenesulfonic acid, and toluene is 100:400:5.0:1.8;

[0097] Take N,N-dimethylacetamide, add polyurethane prepolymer, modified amide, and benzylamine peroxide, mix, and obtain an impregnation solution;

[0098] The mass ratio of polyurethane prepolymer, modified amide and benzyl peroxide is 100:15:0.8; the solid content of the impregnation liquid is 15%;

[0099] The non-woven fabric was immersed in the impregnation liquid for 12 seconds, slowly pulled out, reacted at 85°C for 45 minutes, washed with water, and dried to obtain a surface non-woven fabric;

[0100] Process (2) is the same as in Example 1 to obtain a car trunk carpet.

[0101] Example 3

[0102] (1) Preparation of surface nonwoven fabric:

[0103] 1.1. Preparation of modified polyester:

[0104] The dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and polymerization inhibitor are mixed, the temperature is raised to 220°C at a heating rate of 3°C / min, the reaction is carried out until esterification water appears, the temperature is raised to 250°C at a heating rate of 16°C / h, and the reaction is carried out at a constant temperature until the acid value reaches 0.5 mgKOH / g, thereby obtaining a hydroxyl-containing unsaturated polyester;

[0105] The unsaturated diol is a mixture of butene glycol, 1,5-hexadiene-3,4-diol and 2-vinyl propane-1,3-diol in equal weights; the saturated diol is ethylene glycol; the inhibitor is p-hydroxyanisole; the catalyst is stannous octoate; the mass ratio of dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and inhibitor is 100:100:18:0.4:0.023;

[0106] The hydroxyl-containing unsaturated polyester, ABS and AIBN were mixed, and the mixture was kneaded at a speed of 120 rpm for 10 min at a kneading temperature of 200° C. to obtain the hydroxyl-containing polyester;

[0107] The mass ratio of hydroxyl-containing unsaturated polyester, ABS, and AIBN is 100:18:0.8;

[0108] Take the hydroxyl-containing polyester, add tetrahydrofuran, allyl glycidyl ether, toluene, and phosphazene base under the protection of argon atmosphere, and react at 60°C for 48 hours to obtain unsaturated polyester;

[0109] The mass ratio of hydroxyl-containing polyester, allyl glycidyl ether, and phosphazene base is 1:1.0:18.6; the volume ratio of tetrahydrofuran and toluene is 25:1; the ratio of modified polyester and tetrahydrofuran is 2.0 g / mL;

[0110] In a nitrogen atmosphere, mercaptopropylmethyldimethoxysilane, anhydrous ethanol and deionized water were mixed, the pH was adjusted to 5 with hydrochloric acid, the temperature was raised to 64°C, the reaction was performed for 4.5 hours, and the mixture was dried in vacuo to obtain mercaptopolysiloxane; the mass ratio of anhydrous ethanol to deionized water was 6.2:1;

[0111] Take mercaptopolysiloxane, unsaturated polyester and azobisisobutyronitrile, and knead them at a speed of 120 rpm for 10 minutes in a nitrogen atmosphere at a kneading temperature of 200° C. to obtain a modified polyester; the molar ratio of mercaptopropylmethyldimethoxysilane, allyl glycidyl ether and azobisisobutyronitrile is 1.1:1:0.05;

[0112] 1.2. Preparation of surface non-woven fabric:

[0113] The modified polyester and polyethylene oxide were mixed, N,N-dimethylformamide and water were added, and the mixture was stirred at 60°C for 24 hours to obtain a spinning solution; the electrospinning process was as follows: the voltage was 15 kV, the receiving distance was 20 cm, and the propulsion speed of the micro-flow injection pump was 2.0 mL / h; the water washing process was as follows: ultrasonic water washing at 65°C for 60 minutes, and vacuum drying at 75°C for 60 minutes to obtain the modified polyester fiber;

[0114] The mass ratio of modified polyester and polyethylene oxide is 100:10; the mass ratio of N,N-dimethylformamide and water is 100:3.92, and the solid content of the spinning solution is 26.0%;

[0115] The modified polyester fibers are mixed, carded, laid, and spunlaced to obtain a nonwoven fabric; the length of the modified polyester fibers is 51 mm; the weight of the nonwoven fabric is 120 g / m 2 ;

[0116] Take toluene diisocyanate, dibutyltin dilaurate, and ethyl acetate, heat to 55°C, slowly add trimethylolpropane in a nitrogen atmosphere, heat to 80°C, and react for 2.5 hours to obtain a polyurethane prepolymer;

[0117] The mass ratio of toluene diisocyanate, trimethylolpropane, and dibutyltin dilaurate is 100:27:1.0; the ratio of toluene diisocyanate and ethyl acetate is 0.30 g / mL;

[0118] In a nitrogen atmosphere, diethanolamine and N,N-dimethylacetamide were mixed, and a solution of succinic anhydride in N,N-dimethylacetamide was slowly added, and the mixture was reacted for 4.5 hours to obtain a monomer; the monomer and hydroxyl-containing polyester were mixed, and p-toluenesulfonic acid and toluene were added, and the mixture was heated to 145°C and refluxed for 8 hours to obtain a modified amide;

[0119] The molar ratio of diethanolamine to succinic anhydride is 1:1; the ratio of diethanolamine to N,N-dimethylacetamide is 0.90 g / mL; the ratio of succinic anhydride to N,N-dimethylacetamide in the N,N-dimethylacetamide solution of succinic anhydride is 0.25 g / mL; the molar ratio of the monomer, hydroxyl-containing polyester, p-toluenesulfonic acid, and toluene is 100:600:5.3:2.0;

[0120] Take N,N-dimethylacetamide, add polyurethane prepolymer, modified amide, and benzylamine peroxide, mix, and obtain an impregnation solution;

[0121] The mass ratio of polyurethane prepolymer, modified amide and benzylamine peroxide is 100:20:1.0; the solid content of the impregnation liquid is 20%;

[0122] The non-woven fabric was immersed in the impregnation liquid for 15 seconds, slowly pulled out, reacted at 90°C for 60 minutes, washed with water, and dried to obtain a surface non-woven fabric;

[0123] Process (2) is the same as in Example 1 to obtain a car trunk carpet.

[0124] Comparative Example 1

[0125] (1) Preparation of surface nonwoven fabric:

[0126] 1.1. Preparation of modified polyester:

[0127] Take dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and polymerization inhibitor, mix them, heat them to 130°C at a heating rate of 2°C / min, react until esterification water appears, heat them to 230°C at a heating rate of 10°C / h, and react at a constant temperature until the acid value reaches 2.0 mgKOH / g to obtain hydroxyl-containing unsaturated polyester; the unsaturated diol is an equal-mass mixture of 1,5-hexadiene-2,5-diol, 2-vinylpropane-1,3-diol and 1,7-octadiene-2,6-diol; the saturated diol is ethylene glycol; the polymerization inhibitor is hydroquinone; the catalyst is monobutyl tin oxide; the mass ratio of dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and polymerization inhibitor is 100:40:96:0.1:0.016;

[0128] The hydroxyl-containing unsaturated polyester, ABS and AIBN were mixed, and kneaded at 180° C. and 80 rpm for 8 minutes to obtain the hydroxyl-containing polyester; the mass ratio of the hydroxyl-containing unsaturated polyester, ABS and AIBN was 100:12:0.5;

[0129] Take a hydroxyl-containing polyester, add tetrahydrofuran, allyl glycidyl ether, toluene, and phosphazene base under the protection of argon atmosphere, and react at a constant temperature of 50°C for 48 hours to obtain a modified polyester; the mass ratio of the hydroxyl-containing polyester, allyl glycidyl ether, and phosphazene base is 1:0.9:18.2; the volume ratio of tetrahydrofuran and toluene is 20:1; the ratio of the modified polyester and tetrahydrofuran is 1.6 g / mL.

[0130] Comparative Example 2

[0131] (1) Preparation of surface nonwoven fabric:

[0132] 1.1. Preparation of modified polyester:

[0133] Take dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and polymerization inhibitor, mix them, heat them to 130°C at a heating rate of 2°C / min, react until esterification water appears, heat them to 230°C at a heating rate of 10°C / h, and react at a constant temperature until the acid value reaches 2.0 mgKOH / g to obtain hydroxyl-containing unsaturated polyester; the unsaturated diol is an equal-mass mixture of 1,5-hexadiene-2,5-diol, 2-vinylpropane-1,3-diol and 1,7-octadiene-2,6-diol; the saturated diol is ethylene glycol; the polymerization inhibitor is hydroquinone; the catalyst is monobutyl tin oxide; the mass ratio of dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and polymerization inhibitor is 100:40:96:0.1:0.016;

[0134] The hydroxyl-containing unsaturated polyester, ABS and AIBN were mixed and kneaded at 180° C. and 80 rpm for 8 minutes to obtain a modified polyester; the mass ratio of the hydroxyl-containing unsaturated polyester, ABS and AIBN was 100:12:0.5;

[0135] Process 1.2 and (2) are the same as in Example 1 to obtain a car trunk carpet.

[0136] Comparative Example 3

[0137] (1) Preparation of surface nonwoven fabric:

[0138] 1.1. Preparation of modified polyester:

[0139] Take dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and polymerization inhibitor, mix them, heat them to 130°C at a heating rate of 2°C / min, react until esterification water appears, heat them to 230°C at a heating rate of 10°C / h, and react at a constant temperature until the acid value reaches 2.0 mgKOH / g to obtain hydroxyl-containing unsaturated polyester; the unsaturated diol is an equal-mass mixture of 1,5-hexadiene-2,5-diol, 2-vinylpropane-1,3-diol and 1,7-octadiene-2,6-diol; the saturated diol is ethylene glycol; the polymerization inhibitor is hydroquinone; the catalyst is monobutyl tin oxide; the mass ratio of dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and polymerization inhibitor is 100:40:96:0.1:0.016;

[0140] In a nitrogen atmosphere, mercaptopropyl methyl dimethoxy silane, anhydrous ethanol and deionized water were mixed, the pH was adjusted to 6 with hydrochloric acid, the temperature was raised to 58°C, the reaction was performed for 3.5 hours, and the mixture was dried in vacuo to obtain mercapto polysiloxane; the mass ratio of anhydrous ethanol to deionized water was 5.5:1; mercapto polysiloxane, hydroxyl-containing unsaturated polyester and azobisisobutyronitrile were mixed and kneaded at a speed of 80 rpm for 8 minutes in a nitrogen atmosphere at a kneading temperature of 180°C to obtain modified polyester; the molar ratio of mercaptopropyl methyl dimethoxy silane, allyl glycidyl ether and azobisisobutyronitrile was 0.8:1:0.03;

[0141] Process 1.2 and (2) are the same as in Example 1 to obtain a car trunk carpet.

[0142] Comparative Example 4

[0143] 1.1. Preparation of modified polyester:

[0144] The dibasic acid terephthalic acid, diol, catalyst and polymerization inhibitor are mixed, heated to 130°C at a heating rate of 2°C / min, reacted until esterification water appears, heated to 230°C at a heating rate of 10°C / h, and reacted at a constant temperature until the acid value reaches 2.0 mgKOH / g to obtain a hydroxyl-containing polyester; the mass ratio of the dibasic acid terephthalic acid, diol, catalyst and polymerization inhibitor is 100:120:0.1:0.016; the diol is ethylene glycol; the polymerization inhibitor is hydroquinone; the catalyst is monobutyl tin oxide;

[0145] Take a hydroxyl-containing polyester, add tetrahydrofuran, allyl glycidyl ether, toluene, and phosphazene base under the protection of argon atmosphere, and react at a constant temperature of 50°C for 48 hours to obtain an unsaturated polyester; the mass ratio of hydroxyl-containing polyester, allyl glycidyl ether, and phosphazene base is 1:0.9:18.2; the volume ratio of tetrahydrofuran and toluene is 20:1; the ratio of modified polyester and tetrahydrofuran is 1.6 g / mL;

[0146] In a nitrogen atmosphere, mercaptopropyl methyl dimethoxy silane, anhydrous ethanol and deionized water were mixed, the pH was adjusted to 6 with hydrochloric acid, the temperature was raised to 58°C, the reaction was performed for 3.5 hours, and vacuum dried to obtain mercapto polysiloxane; the mass ratio of anhydrous ethanol to deionized water was 5.5:1; mercapto polysiloxane, unsaturated polyester and azobisisobutyronitrile were mixed and kneaded at a speed of 80 rpm for 8 minutes in a nitrogen atmosphere at a kneading temperature of 180°C to obtain modified polyester; the molar ratio of mercaptopropyl methyl dimethoxy silane, allyl glycidyl ether and azobisisobutyronitrile was 0.8:1:0.03;

[0147] Process 1.2 and (2) are the same as in Example 1 to obtain a car trunk carpet.

[0148] Comparative Example 5

[0149] 1.1. Preparation of modified polyester:

[0150] The dibasic acid terephthalic acid, diol, catalyst and polymerization inhibitor are mixed, heated to 130°C at a heating rate of 2°C / min, reacted until esterification water appears, heated to 230°C at a heating rate of 10°C / h, and reacted at a constant temperature until the acid value reaches 2.0 mgKOH / g to obtain a hydroxyl-containing unsaturated polyester; the diol is ethylene glycol; the polymerization inhibitor is hydroquinone; the catalyst is monobutyl tin oxide; the mass ratio of the dibasic acid terephthalic acid, diol, catalyst and polymerization inhibitor is 100:120:0.1:0.016;

[0151] Take a hydroxyl-containing polyester, add tetrahydrofuran, allyl glycidyl ether, toluene, and phosphazene base under the protection of argon atmosphere, and react at a constant temperature of 50°C for 48 hours to obtain an unsaturated polyester; the mass ratio of the hydroxyl-containing polyester, allyl glycidyl ether, and phosphazene base is 1:0.9:18.2; the volume ratio of tetrahydrofuran and toluene is 20:1; the ratio of modified polyester and tetrahydrofuran is 1.6 g / mL.

[0152] Comparative Example 6

[0153] PET was used to replace the modified polyester, and process 1.2 and process (2) were the same as in Example 1 to obtain a car trunk carpet.

[0154] Comparative Example 7

[0155] 1.2. Preparation of surface non-woven fabric:

[0156] Take toluene diisocyanate, dibutyltin dilaurate, and ethyl acetate, heat to 50°C, slowly add trimethylolpropane in a nitrogen atmosphere, heat to 75°C, react for 2.0h, and obtain a polyurethane prepolymer; the mass ratio of toluene diisocyanate, trimethylolpropane, and dibutyltin dilaurate is 100:24:0.8; the ratio of toluene diisocyanate to ethyl acetate is 0.25g / mL;

[0157] In a nitrogen atmosphere, diethanolamine and N,N-dimethylacetamide were mixed, and a solution of succinic anhydride in N,N-dimethylacetamide was slowly added, and the mixture was reacted for 3.6 hours to obtain a monomer; the molar ratio of diethanolamine to succinic anhydride was 1:1; the ratio of diethanolamine to N,N-dimethylacetamide was 0.60 g / mL; the ratio of succinic anhydride to N,N-dimethylacetamide in the solution of succinic anhydride in N,N-dimethylacetamide was 0.20 g / mL;

[0158] Take N,N-dimethylacetamide, add polyurethane prepolymer, monomer, benzyl peroxide, mix, and obtain an impregnation liquid; the mass ratio of polyurethane prepolymer, monomer, and benzyl peroxide is 100:10:0.7; the solid content of the impregnation liquid is 10%;

[0159] The non-woven fabric was immersed in the impregnation solution for 10 seconds, slowly pulled out, reacted at 80°C for 30 minutes, washed with water, and dried to obtain a surface non-woven fabric;

[0160] Replace the modified polyester with PET and prepare polyester fiber and non-woven fabric by the same process;

[0161] Process (2) is the same as that of Comparative Example 6 to obtain a car trunk carpet.

[0162] Comparative Example 8

[0163] Replace the modified polyester with PET and prepare polyester fiber and non-woven fabric by the same process;

[0164] 1.2. Preparation of surface non-woven fabric:

[0165] Take toluene diisocyanate, dibutyltin dilaurate, and ethyl acetate, heat to 50°C, slowly add trimethylolpropane in a nitrogen atmosphere, heat to 75°C, react for 2.0h, and obtain a polyurethane prepolymer; the mass ratio of toluene diisocyanate, trimethylolpropane, and dibutyltin dilaurate is 100:24:0.8; the ratio of toluene diisocyanate to ethyl acetate is 0.25g / mL;

[0166] Take N,N-dimethylacetamide, add polyurethane prepolymer, diethanolamine, and benzyl peroxide, mix, and obtain an impregnation liquid; the mass ratio of polyurethane prepolymer, diethanolamine, and benzyl peroxide is 100:10:0.7; the solid content of the impregnation liquid is 10%;

[0167] The non-woven fabric was immersed in the impregnation solution for 10 seconds, slowly pulled out, reacted at 80°C for 30 minutes, washed with water, and dried to obtain a surface non-woven fabric;

[0168] Process (2) is the same as that of Comparative Example 6 to obtain a car trunk carpet.

[0169] experiment

[0170] Take the car trunk carpets obtained in Examples 1-3 and Comparative Examples 1-8 to prepare samples, test their properties and record the test results:

[0171] Bursting strength: Use an electronic fabric strength tester to test the breaking strength of the non-woven fabric on the surface of the sample;

[0172] Wear resistance: The YG(B)522 disc-type fabric wear tester was used to test the wear resistance of the non-woven fabric on the surface of the sample. The number of revolutions at which the sample was worn and cracked was taken as the wear resistance index.

[0173]

[0174]

[0175] According to the data in the above table, we can clearly draw the following conclusions:

[0176] The car trunk carpets obtained in Examples 1-3 were compared with the car trunk carpets obtained in Comparative Examples 1-8. The test results show that:

[0177] 1. Compared with Comparative Example 1, the surface non-woven fabrics of the trunk carpets obtained in Examples 1-3 have more excellent wear resistance, breaking strength and coating adhesion data, which fully demonstrates that the present invention achieves the improvement of the wear resistance, bursting strength and adhesion of the surface non-woven fabrics of the trunk carpets;

[0178] 2. Compared with Example 1, the process and components of the non-woven fabric raw material fibers in Comparative Examples 1-6 were changed; compared with Comparative Example 6, the components and processes of the coating of the surface non-woven fabric in Comparative Examples 7-8 were changed; wherein, the modified polyester prepared in Comparative Examples 1 and 5 could not be spun to form fibers; and as can be seen from the above table, the wear resistance, breaking strength and coating adhesion data of the surface non-woven fabric of the car trunk carpets obtained in Comparative Examples 2-4 and 6-8 were deteriorated, and it can be seen that the setting of the non-woven fabric raw materials, coating components and processes of the present invention can promote the improvement of the wear resistance, bursting strength and adhesion of the surface non-woven fabric of the prepared car trunk carpet.

[0179] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0180] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a lightweight automobile trunk carpet, characterized in that: Including the following processes: (1) Preparation of surface nonwoven fabric: The unsaturated polyester is reacted with mercapto polysiloxane to obtain a modified polyester; the modified polyester is spun to obtain a modified polyester fiber; the modified polyester fiber is mixed and spunlace to obtain a non-woven fabric; the non-woven fabric is impregnated with slurry and dried to obtain a surface non-woven fabric; (2) Preparation of car trunk carpet: Place two layers of surface non-woven fabrics on the upper and lower surfaces of the mold cavity respectively, and inject polypropylene foam material into the mold cavity to obtain a luggage compartment carpet; The unsaturated polyester is prepared by the following process: The dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and polymerization inhibitor are mixed, heated to 130-220°C at a heating rate of 2-3°C / min, reacted until esterification water appears, heated to 230-250°C at a heating rate of 10-16°C / h, reacted at a constant temperature until the acid value reaches 0-2.0 mgKOH / g, and a hydroxyl-containing unsaturated polyester is obtained; The hydroxyl-containing unsaturated polyester, ABS and AIBN are mixed, and kneaded at a temperature of 180 to 200° C. and a rotation speed of 80 to 120 rpm for 8 to 10 minutes to obtain the hydroxyl-containing polyester; Take the hydroxyl-containing polyester, add tetrahydrofuran, allyl glycidyl ether, toluene and phosphazene base under the protection of argon atmosphere, and react at a constant temperature of 50-60°C for 48 hours to obtain an unsaturated polyester.

2. The method for preparing a lightweight automobile trunk carpet according to claim 1, characterized in that: The (1) comprises the following process: 1.

1. Preparation of modified polyester: In a nitrogen atmosphere, mercaptopropylmethyldimethoxysilane, anhydrous ethanol and deionized water were mixed, the pH was adjusted to 5-6 with hydrochloric acid, the temperature was raised to 58-64° C., the reaction was carried out for 3.5-4.5 hours, and the mixture was dried in vacuum to obtain mercaptopolysiloxane; Take mercaptopolysiloxane, unsaturated polyester and azobisisobutyronitrile, and knead them at a speed of 80 to 120 rpm for 8 to 10 minutes in a nitrogen atmosphere at a kneading temperature of 180 to 200° C. to obtain a modified polyester; 1.

2. Preparation of surface non-woven fabric: The modified polyester and polyethylene oxide are mixed, N,N-dimethylformamide and water are added, and the mixture is stirred at 50-60°C for 12-24 hours to obtain a spinning solution; the electrospinning process is as follows: the voltage is 9-15 kV, the receiving distance is 10-20 cm, and the propulsion speed of the micro-flow injection pump is 1.0-2.0 mL / h; the water washing process is as follows: ultrasonic water washing at 55-65°C for 30-60 minutes, and vacuum drying at 70-75°C for 30-60 minutes to obtain the modified polyester fiber; The modified polyester fibers are mixed, carded, laid, and spunlace to obtain a nonwoven fabric; The non-woven fabric is impregnated with the slurry and dried to obtain the surface non-woven fabric.

3. The method for preparing a lightweight automobile trunk carpet according to claim 1, characterized in that: The mass ratio of the dibasic acid terephthalic acid, unsaturated diol, saturated diol, catalyst and inhibitor is 100:(40-100):(18-96):(0.1-0.4):(0.016-0.023).

4. The method for preparing a lightweight automobile trunk carpet according to claim 1, characterized in that: The mass ratio of the hydroxyl-containing unsaturated polyester, ABS and AIBN is 100:(12-18):(0.5-0.8).

5. The method for preparing a lightweight automobile trunk carpet according to claim 1, characterized in that: The mass ratio of the hydroxyl-containing polyester, allyl glycidyl ether and phosphazene base is 1:(0.9-1.0):(18.2-18.6).

6. The method for preparing a lightweight automobile trunk carpet according to claim 2, characterized in that: The slurry dipping process in 1.

2. is as follows: In a nitrogen atmosphere, diethanolamine and N,N-dimethylacetamide were mixed, and a solution of succinic anhydride in N,N-dimethylacetamide was slowly added, and the mixture was reacted for 3.6 to 4.5 hours to obtain a monomer; the monomer and hydroxyl-containing polyester were mixed, and p-toluenesulfonic acid and toluene were added, and the mixture was heated to 140 to 145°C, and the mixture was refluxed for 7 to 8 hours to obtain a modified amide; Take N,N-dimethylacetamide, add polyurethane prepolymer, modified amide, and benzylamine peroxide, mix, and obtain an impregnation solution; Immerse the nonwoven fabric in the impregnation solution for 10 to 15 seconds, slowly pull it out, react at 80 to 90°C for 30 to 60 minutes, wash with water, and dry.

7. The method for preparing a lightweight automobile trunk carpet according to claim 6, characterized in that: The polyurethane prepolymer is prepared from toluene diisocyanate, trimethylolpropane and dibutyltin dilaurate in a mass ratio of 100:(24-27):(0.8-1.0).

8. The method for preparing a lightweight automobile trunk carpet according to claim 6, characterized in that: The mass ratio of the polyurethane prepolymer, the modified amide and the benzylamine peroxide is 100:(10-20):(0.7-1.0).

9. A lightweight automobile trunk carpet prepared according to the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Novel polyester sulfhydrylation and modification method

    CN107652421A

  • Automobile carpet with composite fiber structure and preparation method thereof

    CN114043914A